2016
DOI: 10.1111/pce.12770
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in apoplast composition associated with defence and disease in interactions between Phaseolus vulgaris and the halo blight pathogen Pseudomonas syringae Pv. phaseolicola

Abstract: The apoplast is the arena in which endophytic pathogens such as Pseudomonas syringae grow and interact with plant cells. Using metabolomic and ion analysis techniques, this study shows how the composition of Phaseolus vulgaris leaf apoplastic fluid changes during the first six hours of compatible and incompatible interactions with two strains of P. syringae pv. phaseolicola (Pph) that differ in the presence of the genomic island PPHGI‐1. Leaf inoculation with the avirulent island‐carrying strain Pph 1302A elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(126 citation statements)
references
References 76 publications
7
114
0
5
Order By: Relevance
“…g-Aminobutyric acid (GABA) represents another defenceassociated apoplastic molecule that could affect the expression of the T3SS during pathogenesis (Mirabella et al, 2007;O'Leary et al, 2016). The use of Arabidopsis and tobacco plants altered in GABA metabolism and Pst DC3000 mutants altered in GABA uptake and metabolism that collectively promote higher levels of GABA within bacteria suggest that GABA can also reduce T3E delivery (McCraw et al, 2016;Park et al, 2010).…”
Section: Blocking Of Pti Implementationmentioning
confidence: 99%
“…g-Aminobutyric acid (GABA) represents another defenceassociated apoplastic molecule that could affect the expression of the T3SS during pathogenesis (Mirabella et al, 2007;O'Leary et al, 2016). The use of Arabidopsis and tobacco plants altered in GABA metabolism and Pst DC3000 mutants altered in GABA uptake and metabolism that collectively promote higher levels of GABA within bacteria suggest that GABA can also reduce T3E delivery (McCraw et al, 2016;Park et al, 2010).…”
Section: Blocking Of Pti Implementationmentioning
confidence: 99%
“…Xylem sap is nutrient poor (Fatima and Senthil-Kumar, 2015); most plant carbon is sequestered intracellularly and transported in the phloem. Metabolites are 10-to 100-fold less concentrated in xylem sap than in the phloem or leaf apoplast (Fatima and Senthil-Kumar, 2015;O'Leary et al, 2016). Xylem is also hypoxic, posing further metabolic constraints for R. solanacearum growth (Dalsing et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Reported pH values in the apoplast vary largely depending on the species and the developmental state of the tissue and the used method. For example, values between pH 6.1 in potato leaves (Oja et al 1999) and pH 4.8 in Phaeseolus vulgaris (O'Leary et al 2016) have been reported in the literature. Regarding these pH values, deprotonation of the quinol at the cytoplasmic side of the plasma membrane seems to be the most likely.…”
Section: Discussionmentioning
confidence: 99%